APLIKASI UJIAN ONLINE BERBASIS WEB DI SMA BHAKTI NUSANTARA PALEMBANG - Nyimas Sopiah; Muhammad Theda Amanda; Muhammad Theda Aminto; Alfi Brilian Al Mubarokah; Yusriah Herawati (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
Palembang Bhakti Nusantara High School is one of the High Schools (SMA) that has used information technology in certain activities. Palembang's Bhakti Nusantara High School utilizes technology to facilitate teaching and learning by applying the Online Examination. At present, the exam still conducts tests using paper so that there is a need for further development to help and improve the effectiveness and efficiency of performance carried out in accordance with the business processes that run at the Bhakti Nusantara Palembang High School. This Online Examination is used to facilitate the management of master data needed to support the examination activities and the management of exam master data values. The software development method used is the web engineering method. This Online Examination implementation uses PHP, HTML, CSS, Javascript and MySQL Database Management System (DBMS).